KENDALA BELAJAR MAHASISWA DALAM PENERAPAN PENDEKATAN OPTIC-SCRAP DALAM MATA KULIAH GEOLOGI - Khalila Isnaini; Bigharta Bekti Susetyo (STKIP Subang, 2026)
The OPTIC-SCRAP approach is used to facilitate systematic visual analysis, but learning challenges remain. This study aims to identify how the OPTIC-SCRAP approach is implemented in Geology courses and the learning challenges faced by students using the OPTIC-SCRAP approach. This study employed a quantitative approach with descriptive methods. Purposive sampling was used based on the results of a preliminary spatial literacy test, resulting in 29 undergraduate students from the class of 2025 being selected as the study sample. Data were collected using a Likert-scale questionnaire that underwent validity and reliability testing. Data were then analyzed using descriptive statistics. The test results showed that out of 49 items, 38 were valid, and a Cronbach's Alpha value of 0.941 was obtained. The results indicate that the application of the OPTIC-SCRAP approach over four sessions gradually improved students' abilities, from descriptive to evaluative, and strengthened critical thinking, spatial analysis, and self-confidence, making it effective in problem-solving-based geology learning. Based on the application of OPTIC-SCRAP, learning obstacles are dominated by internal factors with a fairly high category with a score of 60.2 while external factors have a score of 40. If viewed from gender, in terms of internal factors, women have a score of 61.14 with a fairly high category while men have a score of 51.5 with a low category. In terms of external factors, women have a score of 40.90 with a fairly high category while men have a score of 34 with a low category. Based on academic background, social studies students have a fairly high category of learning obstacles in the internal factor with a score of 61.81 and external factors with a score of 41.44, while science students are in the low category with a score of 51 on internal factors and 35 on external factors. Overall, this study confirms that the OPTIC-SCRAP approach is effective in improving the quality of geology learning, but still requires optimization, especially in overcoming learning obstacles originating from students' internal factors so that learning outcomes can be achieved more optimally and evenly.